Prevention of chemotherapy‐induced cachexia by ACVR2B ligand blocking has different effects on heart and skeletal muscle. Issue 2 (11th December 2017) - Hulmi, Juha J.; Nissinen, Tuuli A.; Räsänen, Markus; Degerman, Joni; Lautaoja, Juulia H.; Hemanthakumar, Karthik Amudhala; Backman, Janne T.; Ritvos, Olli; Silvennoinen, Mika; Kivelä, Riikka
Abstract: Background: Toxicity of chemotherapy on skeletal muscles and the heart may significantly contribute to cancer cachexia, mortality, and decreased quality of life. Doxorubicin (DOX) is an effective cytostatic agent, which unfortunately has toxic effects on many healthy tissues. Blocking of activin receptor type IIB (ACVR2B) ligands is an often used strategy to prevent skeletal muscle loss, but its effects on the heart are relatively unknown. Methods: The effects of DOX treatment with or without pre‐treatment with soluble ACVR2B‐Fc (sACVR2B‐Fc) were investigated. The mice were randomly assigned into one of the three groups: (1) vehicle (PBS)‐treated controls, (2) DOX‐treated mice (DOX), and (3) DOX‐treated mice administered with sACVR2B‐Fc during the experiment (DOX + sACVR2B‐Fc). DOX was administered with a cumulative dose of 24 mg/kg during 2 weeks to investigate cachexia outcome in the heart and skeletal muscle. To understand similarities and differences between skeletal and cardiac muscles in their responses to chemotherapy, the tissues were collected 20 h after a single DOX (15 mg/kg) injection and analysed with genome‐wide transcriptomics and mRNA and protein analyses. The combination group was pre‐treated with sACVR2B‐Fc 48 h before DOX administration. Major findings were also studied in mice receiving only sACVR2B‐Fc. Results: The DOX treatment induced similar ( 10%) wasting in skeletal muscle and the heart. However, transcriptional changes in response to DOX were much greater in skeletal muscle. Pathway analysis and unbiased transcription factor analysis showed that p53‐p21‐REDD1 is the main common pathway activated by DOX in both skeletal and cardiac muscles. These changes were attenuated by blocking ACVR2B ligands especially in skeletal muscle. Tceal7 (3‐fold to 5‐fold increase), transferrin receptor (1.5‐fold increase), and Ccl21 (0.6‐fold to 0.9‐fold decrease) were identified as novel genes responsive to blocking ACVR2B ligands. Overall, at the transcriptome level, ACVR2B ligand blocking had only minor influence in the heart while it had marked effects in skeletal muscle. The same was also true for the effects on tissue wasting. This may be explained in part by about 18‐fold higher gene expression of myostatin in skeletal muscle compared with the heart. Conclusions: Cardiac and skeletal muscles display similar atrophy after DOX treatment, but the mechanisms for this may differ between the tissues. The present results suggest that p53‐p21‐REDD1 signalling is the main common DOX‐activated pathway in these tissues and that blocking activin receptor ligands attenuates this response, especially in skeletal muscle supporting the overall stronger effects of this treatment in skeletal muscles.